PENGARUH FREE CASH FLOW DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING - Feriani, Laila Zakiya; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to prove the direct influence of profitability and free cash flow to the firm value and the indirect influence through dividend as the intervening variable. This research applies quantitative research and the research population has been done by using consumer goodsindustry sector manufacturing companieswhich are listed in Indonesia Stock Exchange in 2012-2015 periods. The sample selection has been done by using purposive sampling method and 14 companies (56 firm years) which have met the criteria have been selected as samples. The analysis technique has been carried out by using multiple linear regressions analysis and path analysis with the SPSS 23. The result of this research shows that profitability gives positive and significant influence to the dividend policy and firm value. Free cash flow gives negative and significant influence to the dividend policy. Meanwhile, free cash flow and dividend policy does not give any influence to the firm value. It has been found from the path analysis test that dividend policy does not give any indirect influence through dividend policy.Keywords: profitability, free cash flow, dividend policy, firm value.